Students Proactive Decision-Making Scale (SPDMS-18) - Jusuf Blegur; Mutmainnah; Marleni; Sardin; Tri Syamsijulianto (Emerging Science Journal)
This study uses the analysis, development, implementation, and evaluation research design to innovate the student proactive decision-making scale. Considering the needs analysis, the researcher constructed 18 items validated by five raters and tested on 849 students from various universities in Indonesia. The content validity test used Aiken’s formula, and the inter-rater reliability test used Pearson’s ICC. While the construct validity and reliability test used CB-SEM analysis, and the concurrent validity test used Spearman’s correlation between SPDMS-18 and Melbourne DMQ. The results of content validity proved that 18 items met Aiken’s parameters (0.80-1.00), Pearson’s ICC value = 0.524, and Cronbach alpha value = 0.846. Construct validity testing proves that the SPDMS-18 loading factor values range from 0.709-0.835, Cronbach alpha values range from 0.752-0.835, composite reliability values range from 0.751-0.839, AVE values range from 0.502-0.634, and discriminant validity values range from 0.709-0.797. The GoF test model proves that the Chi-Square/df value = 3.002, RMSEA value = 0.049, SRMR value = 0.027, NFI value = 0.958, TLI value = 0.963, and CFI value = 0.971. The concurrent validity results using Spearman’s correlation confirmed the sig. value = <0.001. Thus, SPDMS-18 has a significant psychometric function with the actual situation. It becomes one of the references lecturers can use to measure, assess, and evaluate students’ proactive decision-making in lectures.